A few-layer graphene for advanced composite PVDF membranes dedicated to water desalination: a comparative study. Issue 10 (1st September 2020) - Frappa, M.; Del Rio Castillo, A. E.; Macedonio, F.; Politano, A.; Drioli, E.; Bonaccorso, F.; Pellegrini, V.; Gugliuzza, A.
Abstract : Better-quality few-layer graphene is prepared for the enhanced performance of nanocomposite membranes dedicated to desalination through a membrane distillation process. Abstract : Membrane distillation is envisaged to be a promising best practice to recover freshwater from seawater with the prospect of building low energy-consuming devices powered by natural and renewable energy sources in remote and less accessible areas. Moreover, there is an additional benefit of integrating this green technology with other well-established operations dedicated to desalination. Today, the development of membrane distillation depends on the productivity–efficiency ratio on a large scale. Despite hydrophobic commercial membranes being widely used, no membrane with suitable morphological and chemical feature is readily available in the market. Thus, there is a real need to identify best practices for developing new efficient membranes for more productive and eco-sustainable membrane distillation devices. Here, we propose engineered few-layer graphene membranes, showing enhanced trans -membrane fluxes and total barrier action against NaCl ions. The obtained performances are linked with filling polymeric membranes with few-layer graphene of 490 nm in lateral size, produced by the wet-jet milling technology. The experimental evidence, together with comparative analyses, confirmed that the use of more largely sized few-layer graphene leads to superior productivity related efficiency trade-off for the membrane distillation process. Herein, it was demonstrated that the quality of exfoliation is a crucial factor for addressing the few-layer graphene supporting the separation capability of the host membranes designed for water desalination.